2021
DOI: 10.17305/bjbms.2021.5783
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional study of CDCA family members in gastric carcinoma with prognostic value

Abstract: Gastric cancer (GC) represents a widespread malignancy, having a poor prognosis, making it necessary to search for reliable biomarkers. Cell Division Cycle Associated protein (CDCA) family, comprising CDCA1-8, acts as a key in tumor progression. However, CDCAs expression and their impact on prognosis in gastric cancer, especially stomach adenocarcinoma (STAD), have not been clarified. Consequently, we carried out a multifaceted study aimed at exploring the CDCAs expression levels and appraising their potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The greatest advantage of these common clinicopathological parameters is their easy accessibility, which enables a more comprehensive and informed determination of patient prognosis. Although the prognostic value of CDCA genes has been investigated in ovarian [ 33 ], hepatocellular [ 9 ], nasopharyngeal [ 11 ], and gastric carcinomas [ 34 ], this study is the first to systematically explore their prognostic significance in KIRP. Kaplan–Meier analysis indicated that patients with KIRP with elevated CDCA genes expressions had undesirable OS, which was also exhibited in many clinical categories according to subgroup survival analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest advantage of these common clinicopathological parameters is their easy accessibility, which enables a more comprehensive and informed determination of patient prognosis. Although the prognostic value of CDCA genes has been investigated in ovarian [ 33 ], hepatocellular [ 9 ], nasopharyngeal [ 11 ], and gastric carcinomas [ 34 ], this study is the first to systematically explore their prognostic significance in KIRP. Kaplan–Meier analysis indicated that patients with KIRP with elevated CDCA genes expressions had undesirable OS, which was also exhibited in many clinical categories according to subgroup survival analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring effective therapeutic targets and diagnostic biomarkers is thus critical for improving drugs' curative effect in treating breast cancer patients. There is growing evidence indicating that the cell division cycle-associated proteins (CDCA) has vital function in tumor progression [6]. CDCA1 is a potential prognosis biomarker in oral cancer [7].…”
Section: Introductionmentioning
confidence: 99%